Communication education strategy to reduce food waste at the consumer level with a focus on fruit and vegetables - Bambasová, Anna; Mokrejšová, Veronika, 1985-; Zeman, Jiří; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This diploma thesis maps the purchasing and consumption behaviour of consumers that results in the production of food waste, specifically in the area of fruit and vegetables. Further, it explores the means that can contribute to a reduction of such waste. The aim of this thesis is to make recommendations to the non-profit organization Zachraň jídlo leading to the development of a communication education strategy targeted at reducing fruit and vegetable waste by consumers.
Vedoucí práce: Veronika Mokrejšová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses